PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGASI (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVSDN 010 PASIR PUTIH KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU - Hardianti, Menik; Alpusari, Mahmud; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. Based on preliminary observation in SDN 010 Pasir Putih Kec. Batang Gansal Kab. Indragiri Hulu found problems in learning in grade IV . The teacher in delivering course material just use the lecture method and assignment, the teacher did not master the subject matter,inadequate learning facilities, learning environment that is unconfortable, and students are more pleased with the subjects that are artistic, so the impact on students learning outcomes are still relatively low and does not meet the standars KKM (70). Based on this problems the preferred solution is to implement cooperative learning type Group Investigation (GI), because the GI Cooperative Learning model is one model of learning that consist of heterogeneous study groups consisting of 4-6 students and each students cooperative together, discuss the task and understand the subject matter of teir investigation so as to enhance the students learning activities.As of the formulation of the problem of reseach is whwther the implementation of Cooperative Learning Type GI can improve learning outcomes IPS grade IV SDN 010 Pasir Putih kec. Batang Gansal kab. Indragiri Hulu. The purpose of this reseach is to improve learning outcomes IPS grade IV SDN 010 Pasir Putih kec. Batang Gansal kab. Indragiri Hulu. Students through the implementation of cooperative Learning model type GI. This type of reseach is classroom action reseach with two cycle, where each cyde consist of two meeting giving the material a daily test sessions. The subject to the study are 28 students, consisting of 17 male students and 11 female students. Data collection techniques of reseach showing the activities of teachers in the second cycle to obtain a score of 27 with very good category. Classical mastery learning cycle I is 64,28% and the second cycle increased to 85,71%. Conclusions of this reseach is through the implementation of Cooperative Learning Model type GI could increase the activity of teachers, students activities and student learning outcomes at IPS grade IV SDN 010 Pasir Putih kec. Batang Gansal kab. Indragiri Hulu. Suggestions that the authors convey that teachers should use Cooperative Learning Model Type GI and a variety of learning media in the learning process.Keyword : the model cooperative learning type GI, learning outcomes.